Assessment of Football Players' Knowledge of the Impact of Oral Health on Physical Performance in Sana'a, Yemen - Al-Jawfi, Ahmed Khaled Ahmed; Al-Dharhani, Nooraldeen Ahmed; Al-Surihy, Al-Bara'a Khaled Hussein; Mansoor, Hashem Mohammed Nasser; Ali, Marwan Gamal Hazza; Al-Neshmi, Mohammed Murad Mohammed; Al-Gaadi, Ayman Mohammed Abdu; Al-Shameri, Shihab Saleh Mohammed; Al-Emad, Osama Abdulsamad Ahmed; Al-Bahr, Osama Noman Farea; Awadah, Amjad Mohammed Ahmed; Al-Hagri, Khaled Mohammed (University of Science and Technology, Sana'a, 2025)
Oral health significantly influences overall physical well-being, particularly among athletes whose performance depends on optimal health. This study aimed to assess the knowledge of football players in Sana'a, Yemen, regarding the relationship between oral health and physical performance. Using surveys and interviews, the study evaluated players' understanding of how oral health conditions, such as dental caries, periodontal disease, and oral infections, may affect physical fitness, energy levels, and performance outcomes. The findings are expected to identify knowledge gaps and provide recommendations for integrating oral health education into athletic training programs. Promoting oral health awareness among football players may contribute to improved general health, better athletic performance, and reduced oral disease-related complications.